Deficiency of the parathyroid hormone‐related peptide nuclear localization and carboxyl terminal sequences leads to premature skin ageing partially mediated by the upregulation of p27. Issue 11 (15th September 2015) - Jiang, Minyue; Chen, Guangpei; Lu, Na; Zhang, Yongjie; Jin, Shulei; Karaplis, Andrew; Goltzman, David; Miao, Dengshun
Abstract: We previously reported that deficiency of the PTHrP nuclear localization sequence (NLS) and C‐terminus in PTHrP knockin (PTHrP KI) mice resulted in premature ageing of skin. P27, a cyclin‐dependent kinase inhibitor, was upregulated in PTHrP KI mice and acted as a downstream target of the PTHrP NLS to regulate the proliferation of vascular smooth muscle cells. To determine the effects of p27 deficiency on premature skin ageing of PTHrP KI mice, we compared the skin phenotypes of PTHrP KI mice to those of p27 knockout (p27 −/− ) mice and to those of double homozygous p27‐deficient and PTHrP KI (p27 −/− PTHrP KI) mice at 2 weeks age. Compared with wild‐type littermates, PTHrP KI mice displayed thinner skin and decreased subcutaneous fat and collagen fibres, decreased skin cell proliferation and increased apoptosis, higher expression of p27, p19 and p53 and lower expression of cyclin E and CDK2, and increased reactive oxygen species levels and decreased antioxidant capacity. Deficiency of p27 in the PTHrP KI mice at least in part corrected the skin premature ageing phenotype resulting in thicker skin and increased subcutaneous fat and collagen. These alternations were associated with higher expression of CDK2 and cyclin E, lower expression of p19 and p53, and enhanced antioxidant capacity with increased skin cell proliferation and inhibition of apoptosis. Our results indicate that the NLS and C‐terminus of PTHrP play a critical role in preventing skin from premature ageing that is partially mediated by p27.